Autoimmune thrombocytopenic purpura after mumps infection - Unal, Sule; Yetgin, Sevgi; Kara, Ateş; Kanra, Güler (The Turkish Journal of Pediatrics, 2005)
Autoimmune thrombocytopenic purpura is estimated to be one of the most common acquired bleeding disorders of children. The pathogenesis involves the generation of autoantibodies against the normally expressed glycoproteins on the platelet membranes. These antibody-coated platelets in turn are destroyed by the spleen and other reticuloendothelial organs. Although the disease can occur without an identifiable etiology, many underlying pathologies, including infections, can be found. We report the mumps virus as a rare etiology of secondary autoimmune thrombocytopenic purpura.